Interpretation of vector coding variability measures: Withinday repeatability and between-subject variation in treadmill running - Stock, H.; Wilson, C.; McLeod, C.; van Emmerik, R.; Preatoni, E. (ISBS Proceedings Archive (Michigan), 2017)
This study investigated the within-day repeatability and between-subject variation of vector coding variability during treadmill running. The lower-limb kinematics of eight male triathletes running at 12 km/h were captured twice on the same day. Mean coupling angle variability across the stride cycle was computed for 20 couplings using the modified vector coding technique. Between-subject variation was calculated from the first data collection and data from both sessions were used to calculate systematic and typical error. Between-subject variation ranged from 1.4° to 3.7°. Systematic errors between sessions were observed for two couplings and typical errors were between 0.6° and 1.9°. The between-subject variation and within-day repeatability of the measures reported will aid the interpretation of vector coding variability in cross-sectional and intervention studies.